2019
DOI: 10.1080/09639284.2019.1697937
|View full text |Cite
|
Sign up to set email alerts
|

The soft skills of accounting graduates: perceptions versus expectations

Abstract: In recent years, changes in business, new technology, and greater competitiveness and dynamism have all resulted in a need for new skills. This study focuses on soft skills in accounting education, exploring the viewpoints of both graduates and employers. Our main question is to better understand if there is a right match between graduates' perceptions and companies' expectations of the skills that are needed. 251 Italian graduates (Department of Management) and 74 Italian joint-stock companies completed a sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
91
0
22

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(124 citation statements)
references
References 56 publications
11
91
0
22
Order By: Relevance
“…Jackson and Meek (2020) highlight that it is the stakeholders' collective responsibility to shape accounting curricula to better prepare students for the future of work and the expectations of the accounting profession. Dolce et al (2020) suggest that specific training programmes should be created for the less developed skills to ensure a proper linkage between theory and practice. Case studies, role-plays, experiential learning, teamwork tasks and extracurricular activities are options that universities can use to do this (Wats & Wats, 2009).…”
Section: The Growing Importance Of Soft Skillsmentioning
confidence: 99%
“…Jackson and Meek (2020) highlight that it is the stakeholders' collective responsibility to shape accounting curricula to better prepare students for the future of work and the expectations of the accounting profession. Dolce et al (2020) suggest that specific training programmes should be created for the less developed skills to ensure a proper linkage between theory and practice. Case studies, role-plays, experiential learning, teamwork tasks and extracurricular activities are options that universities can use to do this (Wats & Wats, 2009).…”
Section: The Growing Importance Of Soft Skillsmentioning
confidence: 99%
“…In this study, soft skills are defined as the "interpersonal, human, people or behavioural skills needed to apply technical skills and knowledge in the workplace" (Weber et al, 2009, p. 356;Villiers, 2010). Prior studies have also established that soft skills have become increasingly important for promotion to higher levels, and that accountant must also possess a high level of technical competence throughout the promotional process in order to reach the point of consideration for partnership (Dolce et al, 2020;Ahmad, 2019;Blanthorne et al, 2005). Within Malaysia National Philosophy of Education, the main goal of education is to produce a balanced and harmonious individual who is intellectually, spiritually, emotionally and physically (MOE, 2013).…”
Section: Students' Skillsmentioning
confidence: 99%
“…In the context of the accounting profession, Dolce et al (2020) elaborates on the need of accounting graduates to expand and upgrade their skills and competencies to adapt and manage advancements in technology, complex business practices and operations, and complex financial reporting frameworks. This is because greater skills of human capital are needed due to the increasing complexities of the business environment.…”
Section: Introductionmentioning
confidence: 99%
“…Because of that, authors such as Schulz (2008) or Thurner and Böttcher (2012), among others, indicated that the lack of attention that these soft skills receive in the education system may alter students' expectations, to the extent that students may not be aware of other important capabilities they have besides cognitive skills. This underestimation of soft skills has also been found to influence students' employment expectations and perceptions regarding the value that employers give to these skills (Dolce, Emanuel, Cisi, & Ghislieri, 2020;Itani & Srour, 2016).…”
Section: Introductionmentioning
confidence: 99%